Mediciones ideales en la mecánica cuántica - Sergio Martínez (Crítica)
As a series of investigations have shown, the interpretation of the change upon measurement in quantum mechanics described by the "projection pastulate", as a purely statistical formula, is clear. This formula, here denoted by VNL, is a version of the conditional expectation in Hilbert spaces, and this mathematical result can be given a salid physical interpretation in terlDl of quantum statistics. The problem of interpretation arises when the formula comes in for interpretation, as a description of what happens to (states of) individual systems in measurement. Usual interpretations see the formula VNL as a description of a class of measurement transformations which are "minimally disturbing". However, a series of arguments show that such an interpretation is seriouslf flawed. (See Teller (1983), Martínez (1988) and references therein.]